High glucose induces FABP3-mediated membrane rigidity via downregulation of SIRT1 - Lee, Seung-Min; Kwak, Ju Yeon; Ryu, Dongryeol; Shin, Yeo Jin; Lee, Younglang; Yang, Yong Ryoul; Lee, Kwang-Pyo; Suh, Jae Myoung; Kwon, Ki-Sun (Biochimica et biophysica acta. General subjects, 2025)
High glucose induces an atypical lipid composition in skeletal muscle, leading to loss of muscle mass and strength. However, the mechanisms underlying this glucose toxicity are not fully understood. Analysis of genes associated with a phenotype using the BXD phenome resource revealed that increased Fabp3 expression in skeletal muscle correlated with hyperglycemia. FABP3 expression was also increased in hyperglycemic mouse models such as leptin-deficient ob/ob, Ins2Akita, and high-fat fed mice, as well as in aged mice. In cultured myotubes, high glucose elevated the mRNA and protein levels of FABP3, which contributes to decreased membrane fluidity, along with other mechanisms. FABP3 expression was dependent on the NAD+/NADH ratio and SIRT1 activity, suggesting a mechanism by which FABP3 is upregulated in hyperglycemic conditions. Our findings propose that FABP3 links hyperglycemia to atypical membrane physicochemical properties, which may weaken contractile and metabolic function, particularly in skeletal muscle. [Display omitted] •Hyperglycemic phenotypes correlate with Fabp3 expression.•High glucose increases FABP3 expression by downregulating NAD+ and SIRT1.•FABP3 contributes to high glucose-induced reduction of membrane fluidity.